Commodity risk assessment of Crataegus monogyna plants from the UK - EFSA Panel on Plant Health (PLH); Claude Bragard; Paula Baptista; Elisavet Chatzivassiliou; Francesco Di Serio; Paolo Gonthier; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Alan MacLeod; Christer Sven Magnusson; Panagiotis Milonas; Juan A Navas‐Cortes; et al. (EFSA Journal)
Abstract The European Commission requested the EFSA Panel on Plant Health to prepare and deliver risk assessments for commodities listed in Commission Implementing Regulation (EU) 2018/2019 as ‘High risk plants, plant products and other objects’. Taking into account the available scientific information, including the technical information provided by the applicant country, this Scientific Opinion covers the plant health risks posed by the following commodities: Crataegus monogyna bare root plants and rooted plants in pots imported into the EU from the UK. A list of pests potentially associated with the commodities was compiled. The relevance of any pest was assessed based on evidence following defined criteria. Only the quarantine pest Erwinia amylovora was selected for further evaluation. For E. amylovora the special requirements specified in the Commission Implementing Regulation (EU) 2019/2072 are fulfilled by the UK and no other pests for further evaluation were selected.